Sodium activates human monocytes via the NADPH oxidase and isolevuglandin formation. Issue 5 (16th July 2020) - Ruggeri Barbaro, Natalia; Van Beusecum, Justin; Xiao, Liang; do Carmo, Luciana; Pitzer, Ashley; Loperena, Roxana; Foss, Jason D; Elijovich, Fernando; Laffer, Cheryl L; Montaniel, Kim R; Galindo, Cristi L; Chen, Wei; et al.
Abstract: Aims: Prior studies have focused on the role of the kidney and vasculature in salt-induced modulation of blood pressure; however, recent data indicate that sodium accumulates in tissues and can activate immune cells. We sought to examine mechanisms by which salt causes activation of human monocytes both in vivo and in vitro . Methods and results: To study the effect of salt in human monocytes, monocytes were isolated from volunteers to perform several in vitro experiments. Exposure of human monocytes to elevated Na + ex vivo caused a co-ordinated response involving isolevuglandin (IsoLG)-adduct formation, acquisition of a dendritic cell (DC)-like morphology, expression of activation markers CD83 and CD16, and increased production of pro-inflammatory cytokines tumour necrosis factor-α, interleukin (IL)-6, and IL-1β. High salt also caused a marked change in monocyte gene expression as detected by RNA sequencing and enhanced monocyte migration to the chemokine CC motif chemokine ligand 5. NADPH-oxidase inhibition attenuated monocyte activation and IsoLG-adduct formation. The increase in IsoLG-adducts correlated with risk factors including body mass index, pulse pressure. Monocytes exposed to high salt stimulated IL-17A production from autologous CD4 + and CD8 + T cells. In addition, to evaluate the effect of salt in vivo, monocytes and T cells isolated from humans were adoptively transferred to immunodeficient NSG mice. Salt feeding of humanized mice caused monocyte-dependent activation of human T cells reflected by proliferation and accumulation of T cells in the bone marrow. Moreover, we performed a cross-sectional study in 70 prehypertensive subjects. Blood was collected for flow cytometric analysis and 23 Na magnetic resonance imaging was performed for tissue sodium measurements. Monocytes from humans with high skin Na + exhibited increased IsoLG-adduct accumulation and CD83 expression. Conclusion: Human monocytes exhibit co-ordinated increases in parameters of activation, conversion to a DC-like phenotype and ability to activate T cells upon both in vitro and in vivo sodium exposure. The ability of monocytes to be activated by sodium is related to in vivo cardiovascular disease risk factors. We therefore propose that in addition to the kidney and vasculature, immune cells like monocytes convey salt-induced cardiovascular risk in humans. Graphical Abstract: